Nexus Between Diaspora Remittances and Economic Growth - Abel, Sanderson; Chiwakaya , Kenneth; Mutonhori , Courage; Muleya, Henry; Roux, Pierre Le (International Journal of Economics and Financial Issues, 2025)
There has been a proliferation of studies seeking to understand the relationship between remittances and economic growth albeit with contradicting outcomes. The study evaluated the impact of remittance inflows on economic growth in Zimbabwe. The Autoregressive Distributed lag model with time series data from 1980 to 2020 was utilised. Apart from remittance inflows the model also included other variables that impact economic growth. Variables such as fixed capital formation, private consumption, foreign direct investment, and private consumption were included as explanatory variables. The results indicated that remittance inflows positively impact economic growth in the short and long run. Fixed capital formation hurts economic growth in the short run, while private consumption was found to have a negative impact on economic growth both in the long run and short run. As the results indicated that remittance inflows spur economic growth, policy concern should focus on increasing remittance inflows in Zimbabwe to promote economic growth.